Comparative Analysis of Potential Soil Degradation in the state of Sergipe - Pinto de Barros, Glauber Vinícius; Barros Gomes, Heliofábio; de Rezende Nascimento, Paulo Sergio; Cavalcante Pinto, David Duarte; dos Santos Silva, Fabrício Daniel; Lisboa Costa, Rafaela (Geo UERJ, 2023)
Performing field studies to assess soil degradation is expensive and time-consuming. Estimates made by numerical models are, therefore, usually preferred by many researchers and professionals that work on this subject. The present study primarily aims to assess the potential soil degradation (PSD) in the state of Sergipe, Brazil, in the years 2000 and 2019, by employing the fuzzy logic in a Geographic Information System (GIS) environment. The proposed model explores cause-effect relationships between specific variables that are known to affect the PSD, based on membership functions and the Fuzzy Gamma Operator (FGO) applied to data relative to geology, geomorphology, declivity, hypsometry, pedology, precipitation, erodibility, enhanced vegetation index (EVI) and land use. Our results show that, among these factors, the ones that most contributed to degradation were geology, geomorphology, pedology and precipitation. However, proper attention should be paid to variables susceptible to changes in the human timescale, such as precipitation, land use and cover and, consequently, the EVI, which were found to be important contributors to the observed increase in PSD along the studied timespan. Of those, especially, land use and cover, as it is a variable closely related to human activities. The cartographic products resulting from this work are also successful in indicating the regions that exhibit the most and the least important factors with respect to the influence on the processes that contribute to soil degradation, proving to be a valuable tool for decision-making in the planning of preventive and mitigating measures.